Development of an e-learning platform to improve learning delivery in a low-resourced clinical ultrasound training setting - Lamprecht, Heinrich Hilgardt (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.